Pembelajaran IPS dengan Menggunakan Model Cooperative Learning Tipe Numbered Heads Together di Sekolah Dasar - Lestari, Nani; Farida S, Farida S; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The research aimed at improving students’ science learning outcomes by using Numbered Heads Together Model at the four grade. The research was conducted at SDN 09 Bandar Buat. The subjects of the research were teachers and 24 four grade students. The research findings showed that there was such improvement on: a) the planning that was 7,2%, b) the implementation, teachers and students’ aspect; that was 13,8%, and c) the students’ learning outcomes; that was 7,08Keywords: IPS, Numbered Heads Together